Cambridge IGCSE economics workbook - Grant, Susan (Cambridge : Cambridge University Press, 2014)
Endorsed by Cambridge International Examinations, Cambridge IGCSE Economics Workbook is designed to help learners develop their understanding of economics, to build up skills and to enable them to assess their progress. The workbook can be used in conjunction with the Cambridge IGCSE Economics textbook (ISBN 9781107612334) by the same author but may also be used independently. It is divided into eight sections which correspond to the sections of the syllabus and the textbook. Each section, in turn, is divided into ten parts.